2021
DOI: 10.24875/ric.20000375
|View full text |Cite
|
Sign up to set email alerts
|

An Epidermal Growth Factor Motif of Developmental Endothelial Locus 1 Protein Inhibits Efficient Angiogenesis in Explanted Squamous Cell Carcinoma In Vivo

Abstract: Background: Cancer gene therapy using a nonviral vector is expected to be repeatable, safe, and inexpensive, and to have longterm effectiveness. Gene therapy using the E3 and C1 (E3C1) domain of developmental endothelial locus-1 (Del1) has been shown to improve prognosis in a mouse transplanted tumor model. Objective: In this study, we examined how this treatment affects angiogenesis in mouse transplanted tumors. Materials and methods: Mouse transplanted tumors (SCCKN human squamous carcinoma cell line) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Intramuscular delivery of a plasmid expressing DEL-1 and the control significantly improved baseline exercise capacity at 30, 90, and 180 days, but there was no difference in outcome measures between the two groups. DEL-1-mediated angiogenesis has also been reported in many other diseases, such as ischemia models, lung adenocarcinoma, retinopathy, squamous cell carcinoma, and psoriasis [119,[124][125][126][127][128][129]. Taken together, these data suggest that DEL-1-regulated angiogenesis may be a target for many diseases, but its clinical value requires further clinical trials to demonstrate.…”
Section: Other Cardiovascular Diseasesmentioning
confidence: 63%
“…Intramuscular delivery of a plasmid expressing DEL-1 and the control significantly improved baseline exercise capacity at 30, 90, and 180 days, but there was no difference in outcome measures between the two groups. DEL-1-mediated angiogenesis has also been reported in many other diseases, such as ischemia models, lung adenocarcinoma, retinopathy, squamous cell carcinoma, and psoriasis [119,[124][125][126][127][128][129]. Taken together, these data suggest that DEL-1-regulated angiogenesis may be a target for many diseases, but its clinical value requires further clinical trials to demonstrate.…”
Section: Other Cardiovascular Diseasesmentioning
confidence: 63%
“…Intramuscular delivery of a plasmid expressing DEL-1 and the control significantly improved baseline exercise capacity at 30, 90, and 180 days, but there was no difference in outcome measures between the two groups. DEL-1-mediated angiogenesis has also been reported in many other diseases, such as ischemia models, lung adenocarcinoma, retinopathy, squamous cell carcinoma, and psoriasis ( 119 , 124 129 ). Taken together, these data suggest that DEL-1-regulated angiogenesis may be a target for many diseases, but its clinical value requires further clinical trials.…”
Section: Del-1 In Cvdsmentioning
confidence: 85%
“…Explanted tumor models were generated as described previously (14)(15)(16)(17)(18). Briefly, Nu/Nu athymic nude mice were injected subcutaneously in the right flank with squamous cell carcinoma KN (SCCKN) cells.…”
Section: Methodsmentioning
confidence: 99%
“…The stroma is essential for parenchymal growth in cancer, as it supplies blood vessels and nutritional support to cancer cells (13). Kitano et al reported that forced expression of a recombinant protein with the third epithelial growth factor (EGF)-like domain (E3) of developmental endothelial locus-1 (Del1), an extracellular matrix protein secreted by endothelial cells, suppressed the growth of explanted squamous cell carcinoma tumors in a mouse model (14)(15)(16)(17)(18). The EGF-like domain includes the amino acid sequence CXDXXXXYXCXC, which reportedly induces apoptosis (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation